2019
DOI: 10.3389/fpls.2019.00235
|View full text |Cite
|
Sign up to set email alerts
|

Cold-Dependent Expression and Alternative Splicing of Arabidopsis Long Non-coding RNAs

Abstract: Plants re-program their gene expression when responding to changing environmental conditions. Besides differential gene expression, extensive alternative splicing (AS) of pre-mRNAs and changes in expression of long non-coding RNAs (lncRNAs) are associated with stress responses. RNA-sequencing of a diel time-series of the initial response of Arabidopsis thaliana rosettes to low temperature showed massive and rapid waves of both transcriptional and AS activity in protein-coding genes. We exploited the high diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 99 publications
1
54
1
Order By: Relevance
“…These results reflect the analysis of the complete time-series (Calixto et al, 2018). Experimental validation of expression, AS and isoform switches by high resolution RT-qPCR and high resolution RT-PCR have been described previously (Calixto et al, 2018(Calixto et al, , 2019.…”
Section: Application Of 3d Rna-seq App To Rna-seq Analyses Of Expresssupporting
confidence: 58%
See 1 more Smart Citation
“…These results reflect the analysis of the complete time-series (Calixto et al, 2018). Experimental validation of expression, AS and isoform switches by high resolution RT-qPCR and high resolution RT-PCR have been described previously (Calixto et al, 2018(Calixto et al, , 2019.…”
Section: Application Of 3d Rna-seq App To Rna-seq Analyses Of Expresssupporting
confidence: 58%
“…The 3D RNA-seq App was applied to selected time-points from time-series RNA-seq data of a study on changes in the Arabidopsis transcriptome in response to cold stress (Supplementary Figure 6) (Calixto et al, 2018(Calixto et al, , 2019. Briefly, 5-week-old Arabidopsis Col-0 plants were grown at 20 o C for 24 hours, then the temperature was reduced to 4 o C. Samples Figure 6A).…”
Section: Application Of 3d Rna-seq App To Rna-seq Analyses Of Expressmentioning
confidence: 99%
“…We used RNAseq data from three biological repeats of five organs/tissues of Morex to quantify transcripts with Salmon and BaRTv1.0-QUASI. Differential expression (DE) at both gene and transcript levels, differential AS (DAS) genes and differential transcript usage (DTU) were analysed using the recently developed 3D RNA-seq App (Calixto et al, 2018(Calixto et al, , 2019Guo et al, personal communication and 2,791 genes showed significant DAS ( Figure 4A&D; Supplementary Table S6). The overlap between DE and DAS genes (those genes regulated by both transcription and AS) was 2,199 such that 592 genes were DAS-only and regulated only at the level of AS with no change in overall gene expression.…”
Section: Differential Expression and Differential Alternative Splicinmentioning
confidence: 99%
“…We used RNAseq data from three biological repeats of five organs/tissues of Morex to quantify transcripts with Salmon and BaRTv1.0-QUASI. Differential expression (DE) at both gene and transcript levels, differential AS (DAS) genes and differential transcript usage (DTU) were analysed using the recently developed 3D RNA-seq App (Calixto et al, 2018(Calixto et al, , 2019Guo et al, personal communication log2 fold change of ≥ 1. To identify significant DAS genes, consistency of expression changes (log2 fold change) between the gene and its transcripts was determined along with the change in splice ratio (Δ Percent Spliced -ΔPS).…”
Section: Differential Expression and Differential Alternative Splicinmentioning
confidence: 99%
See 1 more Smart Citation